Factors Affecting Kenyan Farmers` Decision to Purchase Micro-Insurance - Forichi, Lovemore (My University, 2012)
The objective of this research was to establish factors that affect the decision by farmers in the purchase micro-insurance, with the ultimate goal of making agricultural micro-insurance providers increase their product uptake among farmers. The research was performed in the Narok District of Kenya, which is the bread basket of Kenyan agriculture. Literature review identified 13 key attributes that then formed the composition of the proposition. The focus group method was chosen as the most appropriate research instrument. Focus Group discussions were held and key outcomes were in line with the literature review findings, but with different weights attached to the attributes. The key recommendations are in the majority external influence factors that include: the need for agricultural micro-insurance providers to build trust among their target segment; the need to engage the government institutions as they are the trusted source by the target segment; and the need to tailor make the insurance product and make the price affordable. The individual influences include: the need for enhancement of product knowledge among the target segment; the need to build familiarity with insurance products in general and the need to simplify product offering. The key message is that the farmers in Kenya would like to have an agricultural micro-insurance product that they understand, is reasonably priced, is easily accessible and is distributed by trusted sources.
MBA thesis - WBS
Keywords: Micro-insurance; Insurance; Agriculture, Kenya